Wakaf Dalam Perspektif Undang-Undang Nomor 41 Tahun 2004 - Zainul Arifin; Muhammad Syahri Ramadhan; Irsan (Journal of Economics and Development, 2024)
Waqf functions to realize the potential and economic benefits of waqf assets for the benefit of worship and to advance public welfare. Problems that occur are generally waqf assets requested or taken back by the wakif or the heirs of the wakif, or conversely the waqf assets are controlled for generations by nazhir whose use deviates from the waqf contract, is not responsible for his obligation to maintain waqf assets, abandons or transfer to third parties by way of breaking the law. The use of waqf objects over time is sometimes irrelevant to the original purpose of waqf. Resolution of waqf disputes through methods in accordance with Article 62 of the Waqf Law, namely litigation and non-litigation through deliberations and mediation. The approach in this study uses the normative legal method, which is a process to find legal rules, legal principles, and legal doctrines to answer the legal issues faced.